2015
DOI: 10.1002/clen.201400905
|View full text |Cite
|
Sign up to set email alerts
|

Morpho‐Physiological Growth and Yield Responses of Two Contrasting Maize Cultivars to Cadmium Exposure

Abstract: Increasing soil contamination by cadmium (Cd) has emerged one of the gravest threats to environmental sustainability and global food security. Maize, a major staple food, is supposed as the conspicuous source for intake of Cd by human beings. The present study investigated the morpho‐physiological growth and yield responses of two contrasting maize cultivars (Run Nong 35 and Wan Dan 13) to different Cd toxicity levels (0, 75, 150, 225, 300, and 375 μM). A considerable reduction in the growth and yield performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 45 publications
5
22
0
Order By: Relevance
“…the present study showed that Cd significantly decreased the chlorophyll contents of switchgrass, which is similar with the result of Anjum et al (2015).…”
Section: Effects Of CD On Growth Of Root and Shoot In Switchgrasssupporting
confidence: 90%
See 2 more Smart Citations
“…the present study showed that Cd significantly decreased the chlorophyll contents of switchgrass, which is similar with the result of Anjum et al (2015).…”
Section: Effects Of CD On Growth Of Root and Shoot In Switchgrasssupporting
confidence: 90%
“…The chlorophyll biosynthesis mechanism and the key enzymes involved in it could be impaired by excess Cd, which would hinder the synthesis of chlorophyll. On the other hand, Cd is suggested to destroy chlorophyll by replacing Mg in chlorophyll, which would lead to disintegration of chlorophyll (Shi et al 2012;Anjum et al 2015). The results in Table 2 Effects of cadmium (Cd) on the root length (RL), surface area (RA) and root volume (RV) of different root segments in 0-0.3, 0.3-0.6, 0.6-0.9 and >0.9 mm diameter classes for the two cultivars *P < 0.05, **P < 0.01, ***P < 0.001.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…Relative water contents (RWC) were measured from 20 days after emergence (DAE), to 120 DAE with an interval of 20 days, and then, average was taken to examine final RWC in cotton under studied treatments. For RWC measurement, first, leaf fresh weight (Wf) was measured; following this saturated weight of leaves (Ws) was measured after floating leaves in water for 18 h. Leaf dry weight (Wd) was measured (at 70°C) after drying the leaves in oven for 72 h (Anjum et al 2016). The RWC (%) were computed as…”
Section: Data Collectionmentioning
confidence: 99%
“…Relative water contents (RWC) explain turgidity of cells; however, reduction in turgidity results in reduced leaf water contents and declined water use efficiency (González and González-Vilar 2001). Studies reported that measurement RWC is a good indicator of plant growth and plant leaf gas exchange ability (Jensen et al 2000;Anjum et al 2016).…”
Section: Introductionmentioning
confidence: 99%